Shared Stories: co-authorship and relational perspectives in breast cancer memoirs - Loddo, Mariarosa (Tidsskrift for Forskning i Sygdom og Samfund, 2025)
The essay examines two breast cancer memoirs from a literary perspective: Cancer in Two Voices by Sandra Butler and Barbara Rosenblum (1991), and The Use of Photography by Annie Ernaux and Marc Marie (2005). The comparative analysis of the two texts aims to explore the dual perspective that characterises both works, shedding light on how the notion of kinship acts and is interpreted within them. Furthermore, the inquiry investigates the ethical implications of these collaborative literary projects, ascertaining the presence of different narrative authorities and determining what values and functions are associated with storytelling when a couple experiencing illness decides to write about it. What emerges from the comparison is an extended notion of kinship that gives rise to narratives pervaded by tensions between introspection and acceptance of otherness, the private story and the public dimension, the role of the caregiver and that of the sick person.